Fenomena Insecure dalam Perspektif Al-Qur’an: Kajian Tematik terhadap Ayat-Ayat Psikologis dalam Tafsir Al-Mishbah - Najmu Al Tsaqib Al Rijal; Muhammad Amrullah; Siti Rokhani (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
The phenomenon of insecurity has emerged as a significant psychological issue among the younger generation, particularly in the era of social media and strong societal pressures. This feeling is marked by low self-esteem, anxiety, and the tendency to compare oneself with others. This study aims to explore the concept and resolution of insecurity from a Qur’anic perspective, using a thematic interpretation (tafsir maudhu’i) approach with Tafsir Al-Mishbah by Prof. Quraish Shihab as the primary reference. Employing a qualitative method and literature-based analysis with descriptive-analytical techniques, this research examines relevant verses such as QS. Ali Imran: 139, QS. Fussilat: 30, and QS. Yusuf: 87. The findings reveal that the Qur’an not only addresses matters of worship but also offers deep insight into emotional and psychological struggles. These verses provide inner calm, encouragement amid social pressure, and strengthen optimism about the future. Through his thoughtful and soothing interpretation, Quraish Shihab emphasizes that insecurity is not a sign of weakness but a call to return to Allah and embrace self-acceptance with gratitude.